Understanding institutional barriers in the climate change adaptation planning process of the city of Beirut: vicious cycles and opportunities - Zea-Reyes, Leonardo; Olivotto, Veronica; Bergh, Sylvia I. (Mitigation and adaptation strategies for global change, 2021)
Cities around the world are confronted with the need to put in place climate adaptation policies to protect citizens and properties from climate change impacts. This article applies components of the framework developed by Moser and Ekström ( 2010 ) onto empirical qualitative data to diagnose institutional barriers to climate change adaptation in the Municipality of Beirut, Lebanon. Our approach reveals the presence of two vicious cycles influencing each other. In the first cycle, the root cause barrier is major political interference generating competing priorities and poor individual interest in climate change. A second vicious cycle is derived from feedbacks caused by the first and leading to the absence of a dedicated department where sector specific climate risk information is gathered and shared with other departments, limited knowledge and scientific understanding, as well as a distorted framing or vision, where climate change is considered unrelated to other issues and is to be dealt with at higher levels of government. The article also highlights the need to analyze interlinkages between barriers in order to suggest how to overcome them. The most common way to overcome barriers according to interviewees is through national and international support followed by the creation of a data bank. These opportunities could be explored by national and international policy-makers to break the deadlock in Beirut.